Contributions of artificial intelligence in operational risk management - Carvalho, M. C.; Gonçalves, R.; Lopes da Costa, R.; Pereira, L.; Dias, Á. (International Journal of Intelligent Information Technologies, 2022)
Considering the last decades and several economic crises, Operational Risk is a rising area and companies are slowly realizing that the more they invest on it, the less profits they lose. Artificial Intelligence is the critical topic of the century, wide enough to cover all conceivable areas, bringing easy, cheaper, and more precise ways of doing tasks. This paper reflects the progresses of implementing Artificial Intelligence technologies in the control of Operational Risks. The qualitative research revealed the deficiency of investment, as well as the absence of information concerning the progresses on the AI technologies applicable to OpRisk controls. Obstacles as the lack of human resources capabilities and prioritising other sectors are impediments to this automation. Companies must invest in the OpRisk departments, considering the existing AI solutions that allow the maturation of OpRisk controls and, therefore, to mitigate losses that occur from them.